Human genetics as an approach to the classification of mental diseases - Aníbal Silveira (Arquivos de Neuro-Psiquiatria)
If we try to arrange the many patterns of mental disease as regards the underlying heredological trends it is possible to develop a system disposed as a "natural series". In our tentative one, which combines eugenic and dynamic criteria chiefly, we tried to assemble 24 separate clinical conditions into 5 major groups: I - Psychoses with toxi-infectious diseases (4 entries); II - Psychoses with accidental intoxications (2 entries) ; III - Constitutional endogenous psychoses (7 entries); IV - Marginal endogenous states (7 entries); V - Defective states by local or abiotrophic brain lesions (4 entries). Among the conditions listed under IV are Kleist's marginal or "degenerative" psychoses, which are frequent indeed in psychiatric practice, so to require their consideration.